Electroporation ablation of bronchial smooth muscle cells: A novel non-thermal asthma therapy - Tri, Jason A. (Pulm Crit Care Med, 2016)
OBJECTIVE: Asthma is a common disease which places significant burden on the US healthcare system and which can be associated with significant patient morbidity and mortality. Current medical therapies are costly and not curative. A new approach for a more permanent asthma treatment is the use of radiofrequency ablation. However, this radiofrequency approach is thermal-based and can result in deleterious effects to the airways, such as stenosis or ulceration. We describe a novel, improved therapeutic approach for smooth muscle ablation using non-thermal DC electroporation ablation. METHODS: We developed and tested prototype electroporation ablation devices that access the airways both endoscopically and via a bronchoscope. We tested the feasibility of this approach and demonstrated proof-of-concept in 2 mongrel dogs. In order to assess for smooth muscle function, we performed functional studies pre and post ablation with methacholine challenge to assess for airway reversibility. We also evaluated bronchial lesions via direct vision with bronchoscopy. RESULTS: We developed novel electroporation catheters to delivery energy to the bronchial smooth muscle through an endoscopic approach. We tested these catheters in 2 acute canine studies and successfully demonstrated the ability to destroy smooth muscle tissue via novel prototypes and saline irrigation for widespread non-thermal electroporation ablation. Our functional studies demonstrate the efficacy of this approach. CONCLUSION: We report a novel method for non-thermal bronchial smooth muscle ablation using novel prototypes and electroporation with normal saline. These early findings require further evaluation in larger, chronic canine studies to assess for use as a potential curative therapy.